KETEPATAN REKOMENDASI PADA KASUS VIGNETTE SWAMEDIKASI SAKIT KEPALA OLEH APOTEKER DI APOTEK - Amalia, Nurul; Wibowo, Yosi Irawati; Halim, Steven Victoria; Setiawan, Eko; Irawati, Sylvi; Presley, Bobby; Setiadi, Adji Prayitno; Brata, Cecilia (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Headache is a symptom which people often self-medicate and community pharmacies are often places where self-medicating patients with headache obtain the medicines. Therefore, community pharmacists played an important role in providing appropriate advice for these patients. A cross-sectional study design was used. A questionnaire consisting of (1) pharmacy and pharmacists characteristics, and (2) two vignette cases of headache (tension headache and migraine due to an oral contraceptive) was developed. Data was collected using a structured interview with community pharmacists in an East Javan district. Data was analysed using content analysis. Appropriate recommendation was determined based on the literature and expert panel opinion. The total population was 81 community pharmacists. Of these, 47 agreed to participate. Of 47 participating pharmacists, 36 (77%) and 23 (49%) pharmacists provided appropriate advice in the case of tension headache and migraine due to the use of an oral contraceptive respectively. Appropriate recommendation provided by pharmacists varied according to the cases. Optimization of pharmacists’ recommendation in a case of headache requiring medical referral is needed.